(untitled) (AYUSHDHARA, 2024)
Vibandha is the most common digestive complaint and cause for lot of lifestyle disorders. Almost 70%-80% people struggle with constipation and the market of laxative is growing healthy each year. So, it appears that vibandha is the issue that most of us must deal with, one time or other. This study was aimed to find an affordable and quick relief from Vibandha using Ushnodakapana as well as lifestyle modification. 32 patients who diagnosed as suffering from Vibhanda was divided into two groups as Group -A (study) and Group -B (control). Group A was administered 2 glasses of Ushnodaka given in morning time and Group B was administered 2 glasses of Ushnodaka given in night-time. There was marked and moderate improvement observed in morning group when compared to night group patients. Relief in main complaints like consistency of stools is 45.83% in morning group when compared to 45.83% in night group which is highly significant at (p>0.001), straining is 60% in night group when compared to 58% in morning group which is highly significant at (p>0.001), unsatisfied evacuation is 71.11% in morning group as compared to 61.22% in night group which is highly significant at (p>0.001), daily evacuation is 83.33% in morning group as compared to 80% in night group which is highly significant at (p>0.001). Ushnodaka due to the Vatanulomana, Deepana property relieves Vata and clears the Aama. Therefore, Ushnodakapana can be prescribed as a better solution for Vibhandha.